2014
DOI: 10.1186/s13028-014-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an indirect enzyme-linked immunosorbent assay for serological detection of Schmallenberg virus antibodies in ruminants using whole virus antigen

Abstract: BackgroundIn late 2011, a new Orthobunyavirus of the Simbu serogroup named Schmallenberg virus (SBV) emerged in continental Europe. The virus is transmitted by hematophagous arthropods, with the Culicoides species as, so far known, main vectors. Infection with the virus can cause clinical signs in adult ruminants including diarrhea, fever and reduced milk production. Transplacental infection of the developing fetus can lead to malformations of varying severity. To assess seroprevalence of SBV in Sweden an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(22 reference statements)
1
12
0
1
Order By: Relevance
“…The neutralizing titer of a serum was determined as the highest dilution in which the cell monolayer was intact. A serum sample was considered negative if cpe was observed at and from a dilution of 1:8 [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…The neutralizing titer of a serum was determined as the highest dilution in which the cell monolayer was intact. A serum sample was considered negative if cpe was observed at and from a dilution of 1:8 [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…The antigenic cross-reactivity test results indicated that the indirect ELISA did not cross-react with common bacteria and was capable of detecting anti-sera to Klebsiella pneumoniae. Both the intra-assay and inter assay CVs were lower than 10%,which suggested that the method has good reproducibility [29]. To further evaluate the e cacy of the method, additional tests in clinical veterinary settings are essential.…”
Section: Discussionmentioning
confidence: 99%
“…The competitive ELISA technique has an added advantage of no requirement for sample clean-up and a high sensitivity to differences in composition of complex mixtures of different antigens even in the presence of relatively small quantities of the specific detection antibody [51,52]. Whole virus antigen preparations like the one used in this study have generally been found to be more sensitive than recombinant antigen targets [53,54] but tends to be less specific as a result of higher likelihood of non-specific binding of co-purified cellular proteins and non-target viral proteins [55,56].…”
Section: Discussionmentioning
confidence: 99%